Respuesta :

Answer:

a(n) = 13 - 2n

Step-by-step explanation:

The explicit formula variables are a(n) = a(1) + d (n - 1). The a(1) is your number you started out with, and the d is the common difference. From the recursive formula example, you see that your first number is 11 and your difference is -2.

1. Plug the numbers into the equation : a(n) = 11 - 2 (n - 1)

2. Distribute: a(n) = 11 - 2n + 2

3. Add like terms: a(n) = 13 - 2n

If you want to double check, you can plug 1 into n and see if you get 11. I did this, and I did so it should be correct. Hope this made sense! Have a great day :)

ACCESS MORE